Sekolah Alam Tondo Lino Ngata Toro: Sebuah Model Pendidikan Inovatif untuk Transformasi Budaya Berkelanjutan - Dewiyanti, Fatimah; Hatta, Ikhtiar; Marzuki, Muhammad; Hendra, Hendra (CV. Social Politic Genius (SIGn), 2023)
This research aims to delve deeper into the process of cultural transformation through the educational system of Tondo Lino Ngata Toro Nature School. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that the Tondo Lino Ngata Toro Nature School is an educational innovation that combines local wisdom values with interactive and experiential learning methods. Arising from the Ngata Toro indigenous people’s need to preserve their culture amidst modernization, this school adopts a holistic approach to education, enriching the curriculum with traditional values and local wisdom practices. The outdoor learning process, designed to involve students through a learn-through-play method actively, ensures that they acquire knowledge and develop deep connections with their environment and community. This initiative demonstrates that education rooted in local wisdom and implemented through direct experiences in the outdoors can be an effective tool for sustainable cultural transformation. Therefore, it is recommended that the Village Government, Traditional Institutions, Community Leaders, and the Ngata Toro indigenous people continue to support and develop the Tondo Lino Ngata Toro Nature School. Strengthening collaboration among various parties is necessary to enrich learning resources and ensure the sustainability of this program. Ideally, the local natural resources and wisdom should be utilized as significant assets in the curriculum by providing more outdoor learning opportunities and incorporating more aspects of local culture into the learning process. Additionally, developing training for facilitators and teachers on experiential learning methods and learn-through-play will enhance the quality of education and the learning experience for students. Finally, encouraging active community participation in the school program will strengthen the relationship between the school and the community and support transmitting cultural values to the younger generation.